Nursing Interventions for the Prevention and Management of Peripherally Inserted Central Catheter Complications: An Integrative Review - Sarika, Adduri; Bhardwaj, Priya; Acharya, Nirmika; Sharma, Anu; Pathak, Rajnish Ashok; Yadav, Prachi; Das, Sonali; KC, Dr. Anitha (International Journal of Aquatic Research and Environmental Studies, 2026)
Peripherally inserted central catheters (PICCs) are essential vascular access devices used for long-term intravenous therapy, chemotherapy, parenteral nutrition, and administration of blood products. Despite their clinical benefits, PICCs are associated with complications including catheter-related bloodstream infections, thrombosis, occlusion, migration, dislodgement, and skin injury. Nurses play a central role in preventing and managing these complications through evidence-based assessment, maintenance, surveillance, patient education, and clinical decision-making. This integrative review synthesizes current evidence regarding nursing interventions that improve PICC outcomes. The review highlights the effectiveness of infection prevention bundles, standardized flushing protocols, catheter securement strategies, patient education programs, and competency-based nursing training. Findings indicate that adherence to evidence-based nursing practices significantly reduces complication rates, improves catheter longevity, and enhances patient safety. Investments in vascular access education, quality improvement initiatives, and standardized care protocols are recommended.